Using robotics in education : lessons learned and learning experiences - Goh, Henry; Aris, Baharuddin (Persatuan Teknologi Pendidikan Malaysia, 2007)
This paper investigates the use of robotics as a vehicle for guiding secondary school students toward an effective understanding of programming and engineering principles. The students built their robots using RCX LEGO MindStorms for a competition in the Robot Transporter Event. The paper describes the lessons learned in terms of designing the robots and learning that has emerged from the studentsâ€™ experiences in building and programming robots. It observes some considerations contributing to an efficient design of the robots and how students find robotics as interesting, fun, â€œcoolâ€?, stimulating and motivating. These conclusions arise from the observations and interviews conducted with six participating students.